Edukasi Pengelolaan Sampah Organik dan Non Organik pada Siswa Siswi - Kinasih, Ayang; Mariana, Erni; Qomariyah, Siti; Rosyidah, Ummi; Ayuwanti, Irma; Wardany, Kusuma (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasing waste problem is a major challenge for Indonesia, which mirrors the situation in many countries around the world. Indonesia's continuous population growth directly contributes to the increasing volume of waste produced every day, thus exacerbating the problem. The waste problem in Indonesia is a major concern, but public awareness is still lacking. Waste management education from an early age is needed to minimize its negative impacts. Community service activities at SDN 2 Pakuan Aji aim to improve students' understanding of waste sorting through education and direct practice. Students are taught to sort waste into organic and non-organic bins. The expected result is an increase in students' understanding and application of waste management. Subsequent activities can be focused on waste processing and recycling practices. This community service activity received a positive response from the school community and succeeded in fostering environmental awareness among students from an early age. In addition, this activity is also effective in increasing students' creativity through the process of recycling organic and non-organic waste materials.